How Well Do Large‐Eddy Simulations and Global Climate Models Represent Observed Boundary Layer Structures and Low Clouds Over the Summertime Southern Ocean?. (17th November 2020) - Atlas, R. L.; Bretherton, C. S.; Blossey, P. N.; Gettelman, A.; Bardeen, C.; Lin, Pu; Ming, Yi
Abstract: Climate models struggle to accurately represent the highly reflective boundary layer clouds overlying the remote and stormy Southern Ocean. We use in situ aircraft observations from the Southern Ocean Clouds, Radiation and Aerosol Transport Experimental Study (SOCRATES) to evaluate Southern Ocean clouds in a cloud‐resolving large‐eddy simulation (LES) and two coarse resolution global atmospheric models, the CESM Community Atmosphere Model (CAM6) and the GFDL Atmosphere Model (AM4), run in a nudged hindcast framework. We develop six case studies from SOCRATES data which span the range of observed cloud and boundary layer properties. For each case, the LES is run once forced purely using reanalysis data (fifth generation European Centre for Medium‐Range Weather Forecasts atmospheric reanalysis, "ERA5 based") and once strongly nudged to an aircraft profile("Obs based"). The ERA5‐based LES can be compared with the global models, which are also nudged to reanalysis data and are better for simulating cumulus. The Obs‐based LES closely matches an observed cloud profile and is useful for microphysical comparisons and sensitivity tests and simulating multilayer stratiform clouds. We use two‐moment Morrison microphysics in the LES and find that it simulates too few frozen particles in clouds occurring within the Hallett‐Mossop temperature range. We tweak the Hallett‐Mossop parameterization so that it activates within boundary layer clouds, and we achieve better agreement between observed and simulated microphysics. The nudged global climate models (GCMs) simulate liquid‐dominated mixed‐phase clouds in the stratiform cases but excessively glaciate cumulus clouds. Both GCMs struggle to represent two‐layer clouds, and CAM6 has low droplet concentrations in all cases and underpredicts stratiform cloud‐driven turbulence. Plain Language Summary: The Southern Ocean, the wide band of water North of Antarctica, is the stormiest place on Earth. Weather systems constantly whirl the atmosphere and blanket the ocean in clouds. Low‐lying clouds reflect sunlight back to space and cool the Earth. Here, we investigate how well the computer models that we use to understand the climate and to forecast future climates can simulate these clouds. We use recent aircraft measurements from the Southern Ocean Clouds, Radiation and Aerosol Transport Experimental Study (SOCRATES) to evaluate two leading U.S. global climate models, the GFDL Atmosphere Model (AM4) and the CESM Community Atmosphere Model (CAM6). We additionally run detailed simulations of Southern Ocean clouds over a small area to understand which physical processes are relevant to cloud formation. We find that our detailed simulations include most of the physics that is relevant to low‐lying Southern Ocean clouds, but one particular type of ice multiplication process, called Hallett‐Mossop rime splintering, is not active enough. CAM6 and AM4 make too much ice in, or glaciate, cumulus clouds. CAM6 has too few cloud droplets, and we hypothesize that this is caused by glaciation and by the simulated clouds driving too little turbulent mixing of the atmosphere. Key Points: SAM LES represents diverse Southern Ocean boundary layer and cloud structures well CAM6 and AM4 maintain supercooled water in stratiform clouds but excessively glaciate cumuli CAM6 underpredicts stratiform cloud‐driven turbulence and cloud droplet concentration